Pengaruh Penerapan SIMAKDA, SPI, dan Kompetensi SDM terhadap Kualitas Laporan Keuangan Daerah - Roshani (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study is to analyze whether the implementation of regional accounting management information systems, internal control systems, and human resource competencies affect the quality of the West Kalimantan Province SKPD report. The sample of this study was conducted by using purposive sampling method. The samples of data used in this study were 40 people. Research data and hypotheses in this study were analyzed using multiple linear regression analysis methods. The results of this study indicated that simultaneous regional accounting management information systems, internal control systems, and human resource competencies sifnificantly influence the quality of regional government financial reports. Meanwhile partially, the internal control system does not significantly influence the quality of regional government financial reports, while the regional accounting management information system and internal control system significantly influence the quality of regional government financial reports.